Blind trust : how parents with a sick child can escape the lies, hypocrisy and false promised of researchers and the regulatory authorities /: how parents with a sick child can escape the lies, hypocrisy and false promised of researchers and the regulatory authorities. (2022) - Rose, Klaus, 1953-
No abstract available